Iliac wing osteochondroma in a 16-year-old boy: a case report - Kulkarni, Shrihari L.; Mannual, Sunil; Daragad, Manjunath S.; Girirajaiah, Sharan H. (International Journal of Research in Orthopaedics, 2020)
Osteochondroma is the most common benign bone tumour. Commonly seen in the long bones of the lower extremity. Ilium is a rare site. We present a 16-year-old boy with swelling in the right groin for 8 months. After clinical and radiological evaluation, it was diagnosed as osteochondroma of right iliac wing. Patient underwent en-bloc excision of the lesion and histopathology confirmed the diagnosis. Pelvic osteochondroma is a rare entity but not unusual. Extra periosteal en-bloc excision is the management of choice in patients with cosmetic deformity, neurovascular compression and malignant transformation with very low recurrence rate.